Spinal afferent neurons: emerging regulators of energy balance and metabolism - Jarrah, Mohammad; Tasabehji, Dana; Fraer, Aviva; Mokadem, Mohamad (Frontiers in Molecular Neuroscience, 2024)
Recent advancements in neurophysiology have challenged the long-held paradigm that vagal afferents serve as the primary conduits for physiological signals governing food intake and energy expenditure. An expanding body of evidence now illuminates the critical role of spinal afferent neurons in these processes, necessitating a reevaluation of our understanding of energy homeostasis regulation. This comprehensive review synthesizes cutting-edge research elucidating the multifaceted functions of spinal afferent neurons in maintaining metabolic equilibrium. Once predominantly associated with nociception and pathological states, these neurons are now recognized as integral components in the intricate network regulating feeding behavior, nutrient sensing, and energy balance. We explore the role of spinal afferents in food intake and how these neurons contribute to satiation signaling and meal termination through complex gut-brain axis pathways. The review also delves into the developing evidence that spinal afferents play a crucial role in energy expenditure regulation. We explore the ability of these neuronal fibers to carry signals that can modulate feeding behavior as well as adaptive thermogenesis in adipose tissue influencing basal metabolic rate, and thereby contributing to overall energy balance. This comprehensive analysis not only challenges existing paradigms but also opens new avenues for therapeutic interventions suggesting potential targets for treating metabolic disorders. In conclusion, this review highlights the need for a shift in our understanding of energy homeostasis, positioning spinal afferent neurons as key players in the intricate web of metabolic regulation.